Analisis Media Monitoring terhadap Branding Fore Coffee dan Kopi Kenangan melalui Media Sosial Menggunakan Tools Brand24 - Kusumawardani, Anisa (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Indonesia's coffee industry has grown a lot because more people are using the internet and there is a lot of competition among local brands that use social media to promote their products. Brand24 is a media monitoring tool that will be used in this study to look at how well two top coffee brands, Fore Coffee and Kopi Kenangan, are doing on social media. The study looks at seven important factors from May to June 2025: engagement rate, reach, sentiment analysis, content strategy, hashtag performance, influencer involvement, and brand mentions. It uses a mixed-method methodology. Kopi Kenangan has the most brand mentions (1,667) and social media reach (4.1 million), whereas Fore Coffee has the most positive sentiment (53% vs. 36%) and non-social media coverage. Kopi Kenangan has a volume-driven strategy that focuses on community participation, while Fore Coffee uses episodic marketing to build emotional connections and a high-end brand image. There isn't a clear market leader because both brands have about the same amount of voice. The study says that Kopi Kenangan could work on making its advertising more positive, and Fore Coffee should use its high brand equity to reach more people. The research recommends Kopi Kenangan improve content quality to enhance sentiment, while Fore Coffee should leverage its strong brand equity for more aggressive market expansion. Some problems with this study are that it only looked at two brands and only for a short time. This suggests that further studies should be done in the future.